GE_GERICHTE C/22197/2013 vom 25. April 2016 - GE Cour de justice (2016)
BAIL À LOYER; RÉSILIATION; CONTESTATION DU CONGÉ; CONGÉ DE REPRÉSAILLES; PROLONGATION DU BAIL À LOYER | CO.271a.1; CO.271; CO.272